DEADLOCK AVOIDANCE WITH MODIFIED BANKER’S ALGORITHM TO HANDLE INTERRUPTS - S, Sanjit C K; H, Santhi (International Journal of Psychosocial Rehabilitation, 2020)
Banker’s algorithm is an existing and established algorithm for process deadlock detection in the field of OS. Although it offers a reliable deadlock handling mechanism, it does not by default have the capacity to handle incoming interrupts to the OS. Through this paper, I aim to create a modified bankers algorithm with the added functionality to handle interrupts. Further, the simulation is done with the help of posix, multithreading module in C/C++ - pthreads.